REHABILITASI DAN REKONTRUKSI PASCA GEMPA BUMI TAHUN 2006 PADA UMKM GERABAH DI DESA MELIKAN KECAMATAN WEDI KABUPATEN KLATEN - Suharyanto Suharyanto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2011)
Earthquake on May 27th, 2006 had destroyed the various sectors of the economy, especially SMEs in several areas, including pottery SMEs in Klaten Regency. The purpose of this study was to 1). Describe the post-reconstruction condition of SMEs conducted by various parties in restoring the condition of pottery’s MSME in Wedi District, 2). Describe the initiative and community participation in supporting the successful Wedi District pottery’s MSME reconstruction. The study was a descriptive qualitative method of discourse analysis. The results of this study is that reconstruction efforts are carried out by various parties has not been able to restore the conditions of SME in accordance with the original pottery, on the other hand people have participated well in the reconstruction and rehabilitation efforts. Hurdles are the lack of capital, marketing and government support.